ANALYSIS HOTS CONTENT IN ERLANGGA STRAIGHT POINT SERIES (ESPS) 5TH GRADE MATHEMATICS TEXTBOOK BASE ON BLOOM’S TAXONOMY THEORY - Aan Nurhasanah; Febby Fajar Nugraha; Sulaeman Adi Wijayatna (Kopertis Region IV Jabar and Banten, 2023)
This research is motivated by high-level thinking skills that must be achieved so that the learning process can produce students who are competent in their fields. Therefore, students need to be familiarized with learning activities that can train and improve students' higher order thinking skills. The method used is Content Analysis with a qualitative approach. Based on the results of the study, it was found that 56% of HOTS content in all of the material in this book, with details of 50% C4 (Analyzing), 2% C5 (Evaluating), 4% C6 (Creating), and 44% of material not including HOTS content, so it can be concluded HOTS content of all material in the mathematics textbook Erlangga straight point series (ESPS) class 5 is included in the category (C Medium). Furthermore, the research results obtained 50% HOTS content in all examples of this book's questions, with details of 47% C4 (Analyzing), 1% C5 (Evaluating), 2% C6 (Creating), and 50% of sample questions not including HOTS content, so It can be concluded that the HOTS content of all sample questions in the Erlangga Straight Point Series (ESPS) mathematics textbook for class V belongs to the category (C Medium). Furthermore, the results of the study obtained that 26% of HOTS content in all practice questions in this book, with details of 19% C4 (Analyzing), 1% C5 (Evaluating), 6% C6 (Creating), and 74% of practice questions are not included in HOTS content, so that It can be concluded that the HOTS content of all practice questions in the Erlangga Straight Point Series (ESPS) mathematics textbook for class V belongs to the category (E Very Low).